Scanning European Needs and Expectations Related to Livestock Biosecurity Training by Using the World Café Method - Saegerman, Claude; Niemi, Jarkko K.; De Briyne, Nancy; Jansen, Wiebke; Cantaloube, Alain; Heylen, Marcel; Niine, Tarmo; Jerab, Julia Gabrielle; Allepuz, Alberto; Chantziaras, Ilias; Rodrigues da Costa, Maria; Humblet, Marie-France; et al. (Hindawi, 2024)
The European Union Animal Health Law (2016/429) emphasizes disease prevention, underpinned by livestock biosecurity, surveillance, and traceability, as key aspects to minimize the risk of animal diseases. An important element of biosecurity is the training of key actors involved in implementing it. However, their needs and expectations regarding this training are poorly known. Under the COST action BETTER (CA20103), a World Café was organized to identify the needs and expectations of biosecurity training for farmers, veterinary practitioners, veterinary students, and other actors. A total of 78 participants distributed in four groups participated in the World Café. Needs and expectations were identified and ranked in decreasing order of importance. For farmers, the most important aspects were training focusing on practical aspects, the planning of training sessions in the day to accommodate workload, the need to prepare multiple reminders of upcoming training, and the short duration of events. For veterinary practitioners, it was considered that a mixed approach, including a theoretical and a practical part where people are invited to create a biosecurity plan and a follow-up report, were the most important features of training. For veterinary students, creating a good knowledge of the main principles of biosecurity was found as an essential element of training. Regarding other actors, gaining an understanding in the spread of pathogens and the repercussions on the cost of animal products that diseases might have (consumers), training on good/best practices of cleaning and disinfection and the development of clear protocols (transporters), and a mixture of formal and informal training and training on communication skills (other actors) were considered important. The World Café was a useful method to have a first identification, discussion, and differentiation on livestock biosecurity training needs and expectations of the key actors, although additional follow-up research involving more participants from more diverse countries with different coverage of cultures and education would be beneficial. These needs and expectations are relevant and should be considered when designing new training courses.
Keywords: Biosecurity; Training; Needs; World cafe